99 Left Bundle Branch Block: Is it Time to Reconsider the Criteria for Primary Percutaneous Coronary Intervention?. (3rd June 2016) - Basu, Joyee; Mikhail, Mark; Realey, Tracey; Orr, William
Abstract : Introduction: The European Society of Cardiology includes ST-elevation and presumed new onset left bundle branch block (LBBB) as indications for immediate reperfusion therapy but LBBB may be caused by a number of alternative pathologies. Patients presenting with non ischaemic LBBB are potentially at risk of exposure to unnecessary medication and intervention ultimately leading to increased risk and needless cost. This audit sought to ascertain the proportion of patients presenting with chest pain and LBBB who were confirmed as having acute coronary syndrome (ACS) and how this compared to patients presenting with ST elevation and ST depression/T wave changes. We compared characteristics, such as age and gender and mortality data of patients with and without LBBB. We also explored characteristics that could potentially help to differentiate patients with LBBB into low and high likelihood of ACS. Methods: Data was obtained from our local MINAP database for 3103 patients who presented with chest pain over a 5 year period. Patients with LBBB were identified and demographic data including age and sex, as well as mortality rates were recorded. These factors were directly compared with patients who did not present with LBBB. Numbers of patients with LBBB and ACS were compared to patients presenting with ST elevation as well as ST depression/T wave changes on ECG. Comorbidity data was also examined to identify potential contributors to higher risk. Results: Several factors appear to be useful in stratifying LBBB patients into low and high risk of ACS including previous MI, peripheral vascular disease, cerebrovascular disease, chronic renal failure and whether the patient was a current or ex smoker. Conclusions: Patients presenting with chest pain and LBBB represent only a small proportion of the total burden of ACS. They were not older, were less likely to be male but had significantly higher mortality rates than patients with non-LBBB ECG changes. LBBB triggering Primary PCI activation is only a very small component of the total volume of cases, is a much less accurate predictor of acute coronary occlusion, but is undoubtedly a marker of greatly increased risk of in-hospital mortality and early cardiologist review of these patients in the cath lab may well be beneficial. This audit suggests that further work should be undertaken to better understand the role of LBBB of predicting ACS and acute coronary occlusion in an increasingly elderly population.